Pengaruh Penerapan Asean Corporate Governance Scorecard Terhadap Profitabilitas Perusahaan Terbuka Indonesia Tahun 2021 - Putra, Bryan Yuwanda Lenggana; Adam, Helmy (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This research aims to determine empirical evidence of the effect of implementing ACGS on company profitability. The independent variables used are the Rights of Shareholders, Equitable Treatment of Shareholders, Role of Shareholders, Disclosure and Transparency, and Responsibilities of the Board. ACGS measurements are based on a measurement method used using a purposive sampling method with a sample of public companies that implement ACGS in Indonesia and then measured by the criteria regulated by the ACMF. Data comes from ACGS reports and annual reports. The results of this research state that the rights of shareholders have a positive effect because the company can protect the rights of shareholders in participating effectively in general meetings of shareholders. Furthermore, the equitable treatment of shareholders, the role of shareholders, disclosure and transparency, and responsiveness of the board do not have a significant effect on the company.